2015
DOI: 10.1063/1.4907315
|View full text |Cite
|
Sign up to set email alerts
|

Bandstructure modulation of two-dimensional WSe2 by electric field

Abstract: By means of density functional theory computations, we study band-gap tuning in multi-layer WSe2 sheets by external electric fields. It shows that the fundamental band gap of WSe2 film continuously decreases with an increasing vertical electric field, eventually rendering them metallic. The critical electric fields, at which the semiconductor-to-metal transition occurs, are predicted to be in the range of 0.6–2 V/nm depending on the number of layers. This gap-tuning effect yields a robust relationship, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 70 publications
9
14
0
Order By: Relevance
“…Additionally, the strong perpendicular electric field D, where D = (εTGVTG/dTG − εSGVSG/dSG)/2 where εTG (εSG) is dielectric constant of the top and the bottom hBN and dTG (dSG) is thickness of the top and the bottom hBN, lifts the band edge of at the K point, [34][35][36] and the Γ-K transition can be observed which is also confirmed by our DFT calculations (See S5 for details). Looking at the K point maxima of the valence band under D field, the spin-polarized bands along a perpendicular direction are still existing even under D field and the energy split becomes more resolved.…”
supporting
confidence: 83%
“…Additionally, the strong perpendicular electric field D, where D = (εTGVTG/dTG − εSGVSG/dSG)/2 where εTG (εSG) is dielectric constant of the top and the bottom hBN and dTG (dSG) is thickness of the top and the bottom hBN, lifts the band edge of at the K point, [34][35][36] and the Γ-K transition can be observed which is also confirmed by our DFT calculations (See S5 for details). Looking at the K point maxima of the valence band under D field, the spin-polarized bands along a perpendicular direction are still existing even under D field and the energy split becomes more resolved.…”
supporting
confidence: 83%
“…That is because the concomitant application of large positive V IL and large negative V BG also generates a perpendicular electric field that quenches the band gap, in agreement with previous theoretical calculations [5,9] and our own (see Fig. 1D and 1E and Supplementary Note S7).…”
supporting
confidence: 92%
“…An electric field applied perpendicular to the surface of a bulk semiconductor is screened over a finite length, leaving the material interior unaffected. In atomically thin semiconductors [4], however, the small thickness prevents efficient screening, so that a perpendicular electric field uniformly influences the entire system, modifying its band structure [5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…Molybdenum-and tungsten-based dichalcogenides have been intensively investigated. The band gap variation of a few layers of these materials under electric field have been widely studied [24,[53][54][55][56][57][58][59]. Lebègue et al [60] have reported 2D materials by data filtering from their known bulk structures.…”
Section: Introductionmentioning
confidence: 99%